Evidence for evidentiality - Foolen, Ad; Hoop, Helen de, 1964-; Mulder, Gijs, 1962- (Human cognitive processing, 2018)
"Statements are always under the threat of the potential counter-question How do you know? To pre-empt this question, language users often indicate what kind of access they had to the communicated content: Their own perception, inference from other information, 'hearsay', etc. Such expressions, grammatical or lexical, have been studied in recent years under the cover term of evidentiality research. The present volume contributes 11 new studies to this flourishing field, all exploring evidential phenomena in a range of languages (Dutch, Estonian, Finnish, French, German, Khalkha Mongolian, Spanish, Tibetan, Yurakaré), using a variety of methodologies. Evidential meaning is discussed in relation to other semantic dimensions, such as epistemic modality, semantic roles, commitment, quotative meaning, and tense. The volume is of interest to scholars and students who are interested in up-to-date methods and frameworks for studying evidential meaning and the various ways it is expressed in the languages of the world"--